Testing the validity of the Engel's Law in Montano Village, San Jose, Tacloban City - Luna, Katrina C. (2001)
This study aims to answer the following objectives: 1. to determine the validity of Engel's law as far as its applicability to local conditions is concerned; 2. to determine the income allocation patterns of households in Montano Village and; 3. to establish the relationship of income or change in income and the family expenditure patterns.